Estudo de microscopia eletrônica de transmissão in situ de nanoestrutura de óxidos mistos em altas temperaturas - Maya Johnson, Santiago (2018)
This work addresses the characterization of the high temperature reactions between different nanoparticles oxides, CeO2-ZrO2 and CeO2-SnO2, by the direct observation of the phenomenon by in situ Transmission Electron Microscopy (TEM). The nanoparticles were synthesized via three different synthesis methods, hydrothermal, solvothermal, and solvent-control. The changes in the size and morphology of the nanoparticles, the interactions that lead to processes of sintering / densification, and the phase transformations that occur during the experiments were documented. Also, a detailed study of the influence of the electron beam current density on the sample, and its synergism with the temperature during the in situ experiments was performed. The interactions between the oxide metal nanoparticles and the films of the TEM grids showed a great influence during the in situ tests at high temperature. For the experimental setups tested in this work, the main mechanism of interaction between the nanoparticles was oriented attachment.